Prevalence and associations of adverse childhood experiences with anxiety and depressive symptoms in Indonesia - Arulsamy, Karen; Effendy, Elmeida; Mardhiyah, Sarah; Amin, Mustafa M.; Husada, M. Surya; Camellia, Vita; Stona, Anne-Claire; Finkelstein, Eric Andrew (Frontiers in Public Health, 2025)
BackgroundResearch in Southeast Asia—particularly Indonesia—on the link between adverse childhood experiences and adult mental health remains limited. The current study aims to examine the prevalence of ACEs in Indonesia, associations with anxiety and depressive symptoms among adults, and gender differences.MethodsWe conducted an online cross-sectional survey of 872 Indonesians aged 21–64 years. ACEs were measured using the WHO ACE-IQ, and anxiety and depressive symptoms with the PHQ-2, GAD-2, and their composite PHQ-4. Associations between ACEs and symptoms were analyzed using weighted regression models adjusting for demographic variables.ResultsACEs were highly prevalent (79.5%), most commonly parental separation (50.9%), emotional neglect (39.4%), and sexual abuse (23.1%). Overall, 38.2% reported one ACE, 22.0% two, and 19.4% three or more. The experience of any ACE is associated with a 0.57-point increase (95% CI = 0.22–0.91) on the GAD-2 and a 0.59-point increase (95% CI = 0.30–0.88) on the PHQ-2. Any ACE is associated with a 10.0 percentage point (95% CI = 0.02, 0.18) increase in the likelihood of reporting at least mild symptoms of anxiety and a 6.6 percentage point (95% CI = 0.01–0.13) increase in the likelihood of reporting at least mild symptoms of depression. These associations are largest for individuals with 3 ACEs or more. Women face a disproportionate burden of ACEs, in terms of prevalence and cumulative exposure, and worse mental health symptoms.ConclusionIn summary, these findings highlight the importance of interventions that consider cumulative ACE exposure and adopt gender-sensitive approaches to reduce long-term mental health consequences.